Integration of annual forage legume with maize for better feed availability of livestock in maize dominated mixed farming system of Southern Region, Ethiopia - Edao Shanku; Aman Getiso; Diribi Mijena; Fromsa Ijara (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
This study was conducted at Dore Befano and Meskan district of Sidma regional state and Gurage zone of south nation, nationalities, and peoples of southern Ethiopia's (SNNPR), where maize dominated. The trial was conducted to evaluate the outcome of under sowing lablab on the grain yield, Stover, and appropriate time and seeding rate of forage crop under sowing. The trial was implemented using a 3 by 3 factorial combination with two sole treatments in an RCBD with three replications. The treatments were sole Maize (T1). Sole forage (T2) and Maize & Forage Simultaneous with maize sowing date full Simultaneous with maize sowing date 75%, Simultaneous with maize sowing date at 50%, Maize & Forage After 15 days of maize sowing full, after 15 days of maize sowing 75%, After 15 days of maize sowing 50%, Maize & Forage After 30 days of maize sowing full, Maize & Forage After 30 days of maize sowing 75% and Maize & Forage After 30 days of maize sowing 50% T3 to T11 respectively. Under sowing of lablab with maize did not affect the grain yield of maize. Among experiments, T5 was a more appropriate seeding rate and sowing time for under sowing of lablab with maize.